Evaluation of the anticarcinogenic effect of strawberry (Fragaria x ananassa) on somatic cells of Drosophila melanogaster (Research, Society and Development, 2023)
Carcinogenesis is the process that leads to the formation of cancer, which can occur spontaneously or provoked by the actions of carcinogens. Combined chemoprevention, based on diet, is promising, as well as being more accessible to the population, has lower cost and acts to reduce the risk of cancer. In this context stands out the strawberry (Fragaria x ananassa), with high content of photochemical compounds, with rebound for phenolic compounds and their protective actions. In this context, the present research aimed to evaluate the anticarcinogenic effect of strawberry against damage induced by doxorubicin, through the test for detection of clones of epithelial tumors in somatic cells of Drosophila melanogaster. Two strains of D. melanogaster were used to perform the ETT: Warts and Multiple Wing hairs. The larvae obtained were submitted to carcinogenic evaluation, pre-treatment with strawberry and post-treatment with strawberry, in addition to negative control using reverse osmosis water and positive control of 0.4mm doxorubicin. The results of individuals treated with strawberry of 25%, 50% and 100% presented tumor frequencies of 0.1, 0.15 and 0.21, respectively, while in the pre-treatment with strawberry 50% and 100% and exposed DXR 0.4mm showed frequency of tumors per fly of 0,25 and 0.13 respectively and in the post-treatment there was a reduction in the frequency of tumors, since the higher the concentration, the lower the tumor frequency. It is concluded that the strawberry in the present experimental conditions presented anticarcinogenic effect, which suffered variation of the concentration tested.